Challenges Of Electronic Evidence In Law Enforcement In The Era Of Digital Technology - Guna Harta (jurnal.unprimdn.ac.id, 2026)
Evidence in court plays an important role in a case. This is the basis for judges in viewing a legal event. Criminal acts in the modern era, a sophisticated electronic technology has become a new tool for perpetrators of criminal acts, where these perpetrators take advantage of the complexity and speed of technology. This requires law enforcement officers to rely on electronic evidence (digital evidence) in uncovering a crime. However, the existence of electronic-based evidence in Indonesian criminal procedure law faces fundamental legal challenges, such as in terms of legal construction, authenticity standards, and its application in court. This study aims to analyze the effectiveness of electronic evidence. The definition of evidence in Law 1 of 2024, concerning Amendments to Law Number 11 of 2008 concerning electronic information and transactions (ITE Law). This study uses Normative Jurisprudence with a conceptual legislative approach. The research findings indicate that although electronic evidence has been explicitly recognized as valid evidence, its practical implementation still faces challenges, including doubts among judges regarding its authenticity, technical complexity requiring specialized expertise, and inconsistent presentation standards in court. Further harmonization, socialization, and increased capacity of law enforcement in handling electronic evidence are needed to ensure the effectiveness of money laundering eradication efforts.